FORMING ENTERPRISING INITIATIVE AS A GOAL OF TECHNICAL EDUCATION - MASTALERZ, Elzbieta (Trends in education, 2008)
This paper introduces a model modern-age employee and teacher's activities aimed at molding his or her students into successful and appreciated workers. Their technical abilities, supported by creativity and efficiency, are universal in nature and form a base of pre-career preparation.
Keywords: attitude; initiative; technical education